2005
DOI: 10.1007/s00213-005-2219-1
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in initial sensitivity and acute tolerance predict patterns of chronic drug tolerance to nitrous-oxide-induced hypothermia in rats

Abstract: Rationale: A preventive strategy for drug addiction would benefit from being able to identify vulnerable individuals. Understanding how an individual responds during an initial drug exposure may be useful for predicting how that individual will respond to repeated drug administrations.Objectives: This study investigated whether individual differences in initial drug sensitivity and acute tolerance can predict how chronic tolerance develops.Methods: During an initial 3-h administration of 60% nitrous oxide (N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 75 publications
4
25
0
Order By: Relevance
“…Consistent with our previous work, 19,21-23,29 repeated 90-min 60% N 2 O administrations engendered the development of thermal tolerance, defined as the absence of N 2 O-induced hypothermia, and a subsequent sign-reversal, defined as the occurrence of hyperthermia during drug administration (Fig. 2A,B).…”
Section: Resultssupporting
confidence: 89%
“…Consistent with our previous work, 19,21-23,29 repeated 90-min 60% N 2 O administrations engendered the development of thermal tolerance, defined as the absence of N 2 O-induced hypothermia, and a subsequent sign-reversal, defined as the occurrence of hyperthermia during drug administration (Fig. 2A,B).…”
Section: Resultssupporting
confidence: 89%
“…In addition, this dynamic basis for T core insensitivity to N 2 O was also evident in some animals administered with the two higher N 2 O concentrations, 60 and 75% (see Fig. 4), which typically but not unfailingly induce hypothermia in drug naive rats (Kaiyala et al 2001;Ramsay et al 2005). To our knowledge, this study is the first to demonstrate a systemslevel regulatory basis for what typically would be called initial drug insensitivity at the level of T core .…”
Section: A Systems-level Basis For Initial Drug (In)sensitivitymentioning
confidence: 67%
“…It has been hypothesized previously that regulatory compensation may also blunt the impact of the pharmacological effect on a monitored dependent variable even within an initial drug administration (Haefely 1986). Furthermore, it has been proposed that this process can be sufficiently robust in some individuals as to effectively stabilize the monitored variable during drug administration, yielding the appearance of initial drug insensitivity (Ramsay and Woods 1997;Ramsay et al 2005). To provide a test of these proposals, the present study assessed the changes of T core , HP, and HL during administrations of six steady-state N 2 O concentrations, 0, 15, 30, 50, 60, and 75% N 2 O.…”
Section: Introductionmentioning
confidence: 94%
“…28 Subsequent research revealed that initially insensitive rats exhibited a prompt increase in HP when initially administered N 2 O that was of sufficient magnitude to counter the increase in HL elicited by the N 2 O; 20 i.e., the rats considered ‘initially insensitive’ at the level of Tc were actually initially hyperresponsive at the level of HP with the consequence that there was little or no change of Tc when first exposed to N 2 O. The magnitude of the HP response increases progressively over repeated N 2 O administrations, which contributes to chronic tolerance development, and with additional administrations causes rats to eventually exhibit a hyperthermic overcompensation of Tc.…”
Section: Introductionmentioning
confidence: 99%